2013
DOI: 10.19026/ajfst.5.3169
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Quantitative Descriptive Sensory Honey Analysis: Application to Eucalyptus and Clover Honeys

Abstract: Sensory analysis of bee honey is an important tool for determining its floral origin, for subsequent quality control practices and which ultimately will determine consumer preferences towards this product. A procedure for the selection, training and monitoring of assessors was applied. Unifloraleucalyptus and clover honeys produced in Argentine were assessed using descriptive quantitative analysis. The sensory profiles differentiated clover honey (light, fruity and floral flavor with low intensity) from eucaly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 12 publications
4
13
0
3
Order By: Relevance
“…Ciappini et al . () agree with our results on crystallisation grade pointing out the fine crystallisation of Eucalyptus .…”
Section: Resultssupporting
confidence: 93%
“…Ciappini et al . () agree with our results on crystallisation grade pointing out the fine crystallisation of Eucalyptus .…”
Section: Resultssupporting
confidence: 93%
“…Aroma attributes were grouped into odour families, as recommended by Piana et al (2004) with slight modifications (Ciappini et al, 2013;IRAM 15980-1:2014). Panellists had to select the descriptors they considered appropriate from a list of pre-established words that define honey aroma (Table S1).…”
Section: Sensory Analysismentioning
confidence: 99%
“…Nonetheless, Ciappini et al (2013) have already indicated that clover honeys from Pampeana region (Argentina) could be characterised as a subtle fruity and floral aroma. Only clover honeys showed a significant correlation with the aroma descriptors of the samples analysed (P = 0.012).…”
Section: Correlation Between Aroma Descriptors and Volatile Compoundsmentioning
confidence: 99%
“…The honey samples were tested for odor, taste, appearance and color in comparison to respective references [38]. The panel of assessors was formed by seven people.…”
Section: Sensory Analysismentioning
confidence: 99%